Ventre colonizado: representações da mulher árabe e suas danças na pintura orientalista do século XIX - Paschoal, Nina Ingrid Caputo (2019)
With the purpose to make a reflection about the representation of the women and their dances, this study addresses the 19th century Orientalist painting. As from an extensive bibliographic review and the analysis of nine works of art, understood here as primary sources, we aim to understand the ways in which European colonialist domination has acted in many medium to propagate a racial superiority discourse, which would give it a plausible justification to the Middle East invasions. Thus, I try to demonstrate that these two subjects of the Orientalist painting has been important and expressive manifestations of an ideological content, also responsible for crystallizing stereotypes about dancing, which has remained to the contemporary days, mainly when we refer to the “Belly Dance”